NOVEL CHEMICALLY Amplified NEGATIVE PHOTORESIST COMPOSITIONS AND PREPARATION THEREOF

By combining photoacid dissociable groups and hydroxystyrene homopolymers, the problem of insufficient lithography performance in the prior art is solved, and high sensitivity and thermal stability of light is achieved Improved performance, especially significant reduction in line width roughness (LWR).

CN119119648APending Publication Date: 2024-12-13SHANGHAI ESSENCE TECH CO LTD
View PDF 34 Cites 0 Cited by

Patent Information

Application Number
CN202310692771.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-12
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

There is a lack of simple and easy-to-prepared novel chemical amplification negative photoresist compositions in the prior art, and their photolithographic properties need to be improved.

Method used

A mixture of copolymer (A) and homopolymer (B) is used, wherein the copolymer (A) has a dissolution inhibiting acetyloxy group and a photoacid dissociable group, and the homopolymer (B) is a hydroxystyrene homopolymer , enhance lithography performance is obtained by adjusting its content.

Benefits of technology

Achieved the photolithographic performance improvement in the inherent advantages of thermal stability and high sensitivity, especially by adjusting the proportion of copolymers and homopolymers, the linewidth roughness (LWR) is significantly reduced to more than 40%, 50% %, 60%, 70% reduction effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119119648A_ABST
    Figure CN119119648A_ABST
Patent Text Reader

Abstract

The present invention relates to novel polymers and compositions containing such polymers, thereby providing polymer-based photoresists for various applications in photolithography, such as KrF.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to novel polymers and compositions containing such polymers to provide polymer-based photoresists for various applications in photolithography such as KrF. Background Art

[0002] Chemically amplified negative photoresist compositions generally contain a resin binder, a photoacid generator (PAG), a quencher, a crosslinker, additives, and a solvent(s). Prior art such as IBM's U.S. Patent No. 6,365,321, U.S. Patent No. 4,491,628, U.S. Patent No. 7,951,525, and Shin-Etsu Chemical Co.'s U.S. Patent No. 5,356,753, U.S. Patent No. 5,731,126, and Hitachi's U.S. Patent No. 4,745,169, and TOK's U.S. Patent No. 6,074,962, U.S. Patent No. 5,990,338, U.S. Patent No. 6,749,991, U.S. Patent No. 6,897,012 and JSR's U.S. Patent No. 5,332,650, U.S. Patent No. 6,846,895, U.S. Patent No. 7,041,748, and FujiFilm's U.S. Patent No. 6,376,152, U.S. Patent No. 6,485,883, U.S. Patent No. 6,537,718, U.S. Patent No. 6,103,449 and Hyundai Electronics, U.S. Patent No. 6,589,707, Hitachi U.S. Patent No. 7,659,047, Fujitsu Ltd. U.S. Patent No. 6,027,856, and Samsung Electronic Company U.S. Patent No. 6,872,502. In addition, the following prior art teachings include Shipley Chemical Co. U.S. Patent No. 7,211,365, U.S. Patent No. 6,048,672, U.S. Patent No. 6,800,422, U.S. Patent No. 6,136,501, Sumi tomo Chemical Company U.S. Patent No. 5,800,966, U.S. Patent No. 6,153,349, TOK U.S. Patent No. 6340553, U.S. Patent No. 9,459,528, U.S. Patent No. 6,815,144, U.S. Patent No. 7,172,848, U.S. Patent No. 7,364,831, Clariant U.S. Patent No. 6,576,394, and Kempur Microelectronics, Inc. U.S. Patent No. 9,766,542.

[0003] There is still a need in the art to obtain a new chemically amplified negative photoresist composition comprising a (co)polymer mixture, wherein the (co)polymer structure is simple and easy to prepare, and at the same time, the new chemically amplified negative photoresist composition can achieve improved lithographic performance. Summary of the invention

[0004] The present invention relates to a mixture of two simple and easily prepared polymers. The chemical structures of these polymers are very similar, and therefore their mixture is uniform without phase separation. In addition, by adjusting the content of each polymer in the mixture, the desired properties required for enhanced lithographic performance can be obtained.

[0005] The resulting mixture is used in a chemically amplified negative photoresist having the intrinsic advantages of thermal stability and high sensitivity (photospeed).

[0006] The present invention relates to a novel chemically amplified negative photoresist composition, comprising a mixture of a copolymer (A) and a homopolymer (B), wherein:

[0007] The copolymer (A) is an acetoxystyrene copolymer having a dissolution inhibiting acetoxy group and a photoacid dissociable group or a styrene group;

[0008] The homopolymer (B) is a hydroxystyrene homopolymer.

[0009] Variations in the amounts of copolymer (A) and homopolymer (B) in the blend will provide the desired properties required for enhanced lithographic performance.

[0010] Preferably, the content of copolymer (A) is in the range of 20 to 80% by weight, for example 20 wt. %, 30 wt. %, 40 wt. %, 50 wt. %, 60 wt. %, 70 wt. %, 80 wt. %, etc., based on the total weight of the mixture of copolymer (A) and homopolymer (B).

[0011] Preferably, the content of homopolymer (B) is in the range of 20 to 80% by weight, for example 20 wt. %, 30 wt. %, 40 wt. %, 50 wt. %, 60 wt. %, 70 wt. %, 80 wt. %, etc., based on the total weight of the mixture of copolymer (A) and homopolymer (B).

[0012] The photoacid-dissociable group contained in the copolymer (A) is selected from the following: an alkyl ester group, an alicyclic ester group, or a combination thereof.

[0013] Preferably, the photoacid-dissociable group is a (meth)acrylate group, which means a methacrylate group or an acrylate group.

[0014] Preferably, the photoacid-dissociable group is selected from the following: an alkyl (meth)acrylate group, an alicyclic (meth)acrylate group, or a combination thereof.

[0015] Preferably, the photoacid cleavable group is an alkyl (meth)acrylate group, wherein the alkyl group is selected from the group consisting of methyl, ethyl, propyl, isopropyl, butyl, isobutyl, tert-butyl, pentyl and isopentyl. Preferably, the alkyl group is substituted by a hydroxyl group.

[0016] Preferably, the photoacid-dissociable group is a tert-butyl (meth)acrylate group.

[0017] Preferably, the photoacid-dissociable group is an alicyclic (meth)acrylate group selected from a 1-alkyl-1-cycloalkyl (meth)acrylate group and a 2-alkyl-2-adamantyl (meth)acrylate group.

[0018] Preferably, the photoacid cleavable group is a 1-alkyl-1-cycloalkyl (meth)acrylate group, wherein the alkyl group is selected from the following: methyl, ethyl, propyl, isopropyl, butyl, isobutyl, tert-butyl, pentyl and isopentyl; and the cycloalkyl group is selected from the following: cyclopentyl, cyclohexyl and cycloheptyl.

[0019] Preferably, the photoacid cleavable group is a 2-alkyl-2-adamantyl (meth)acrylate group, wherein the alkyl group is selected from the group consisting of methyl, ethyl, propyl, isopropyl, butyl, isobutyl, tert-butyl, pentyl and isopentyl.

[0020] Preferably, the photoacid-dissociable group is a combination of a 1-alkyl-1-cycloalkyl(meth)acrylate group and / or a 2-alkyl-2-adamantyl(meth)acrylate group and / or a tert-butyl(meth)acrylate group.

[0021] Copolymer (A)

[0022] The copolymer (A) is a random copolymer, and it may be a binary copolymer or a ternary copolymer.

[0023] The copolymer (A) is partially or completely soluble in an alkaline aqueous solution.

[0024] The copolymer (A) is prepared by copolymerization of acetoxystyrene monomer and one or more comonomers.

[0025] The comonomer is selected from the following: (meth)acrylate monomers and styrene monomers. (Meth)acrylate monomers refer to methacrylate monomers or acrylate monomers.

[0026] The copolymer (A) can be prepared by copolymerizing an acetoxystyrene monomer and a (meth)acrylate monomer.

[0027] Alternatively, the copolymer (A) may be prepared by copolymerization of acetoxystyrene monomers and styrene monomers.

[0028] Based on the total moles of the monomers of the copolymer (A), the preferred range of the acetoxystyrene monomer is 50 mol%-90 mol%, for example 50 mol%, 55 mol%, 60 mol%, 65 mol%, 70 mol%, 75 mol%, 80 mol%, 85 mol%, 90 mol%, etc.

[0029] If present, the preferred range of the (meth)acrylate monomer is 10 mol% to 50 mol%, based on the total moles of the monomers of the copolymer (A), for example 10 mol%, 15 mol%, 20 mol%, 25 mol%, 30 mol%, 35 mol%, 40 mol%, 45 mol%, 50 mol%, etc.

[0030] If present, the preferred range of hydroxyethyl methacrylate monomer is 10 mol% to 50 mol%, based on the total moles of monomers of copolymer (A), for example, 10 mol%, 15 mol%, 20 mol%, 25 mol%, 30 mol%, 35 mol%, 40 mol%, 45 mol%, 50 mol%, etc.

[0031] If present, the preferred range of styrene monomer is 10 mol% to 40 mol%, based on the total moles of monomers of copolymer (A), for example 10 mol%, 15 mol%, 20 mol%, 25 mol%, 30 mol%, 35 mol%, 40 mol%, etc.

[0032] The (meth)acrylate monomer is selected from the following: an alkyl (meth)acrylate monomer, or a hydroxyalkyl (meth)acrylate monomer, or an alicyclic (meth)acrylate monomer, or a combination thereof.

[0033] With respect to the alkyl (meth)acrylate monomer, the alkyl group is selected from the group consisting of methyl, ethyl, propyl, isopropyl, butyl, isobutyl, tert-butyl, pentyl, and isopentyl.

[0034] Preferably, the alkyl (meth)acrylate monomer is a methyl (meth)acrylate monomer.

[0035] With respect to the hydroxyalkyl (meth)acrylate monomer, the alkyl group is selected from the group consisting of methyl, ethyl, propyl, isopropyl, butyl, isobutyl, tert-butyl, pentyl, and isopentyl.

[0036] Preferably, the hydroxyalkyl (meth)acrylate monomer is a hydroxyethyl (meth)acrylate monomer.

[0037] Preferably, the alicyclic (meth)acrylate monomer is a γ-butyrolactone-3-yl (meth)acrylate monomer.

[0038] The preparation method of copolymer (A) is well known in the art. Generally, copolymer (A) is prepared by free radical polymerization of acetoxystyrene monomer and one or more comonomers in the presence of a free radical initiator. Preferably, the free radical initiator is AIBN (azobisisobutyronitrile).

[0039] The weight average molecular weight (Mw) of the copolymer (A) is 2000-20,000 Daltons. Preferably, the weight average molecular weight (Mw) of the copolymer (A) is 10,000-18,000 Daltons.

[0040] The weight average molecular weight (Mw) of the copolymer (A) is measured by GPC (gel permeation chromatography).

[0041] GPC (gel permeation chromatography) is used for weight average molecular weight (Mw) determination. The GPC system uses an HPLC constant flow pump (isocratic pump), an automatic sample injector, an RI (refractive index) detector and a micro-polystyrogel column. Monodisperse standards of polystyrene are used to generate a calibration graph for evaluating the Mw of unknown samples.

[0042] The polydispersity of copolymer (A) is 1.2-4.0. Preferably, the polydispersity of copolymer (A) is 1.2 to 3.0.

[0043] Homopolymer (B)

[0044] The preparation method of the homopolymer (B) is well known in the art. Generally, the homopolymer (B) is prepared by saponifying a homopolymer of acetoxystyrene monomer using a base in a polar solvent.

[0045] Preferably, the base may be ammonium hydroxide. Preferably, the polar solvent may be methanol.

[0046] The weight average molecular weight (Mw) of the homopolymer (B) is 2000-20,000 Daltons. Preferably, the weight average molecular weight (Mw) of the homopolymer (B) is 10,000-18,000 Daltons.

[0047] The weight average molecular weight (Mw) of the homopolymer (B) is measured by GPC (gel permeation chromatography).

[0048] GPC (Gel Permeation Chromatography) is used for polymer molecular weight (Mw) determination. The GPC system uses an HPLC constant flow pump, an autosampler, an RI (refractive index) detector, and a micro polystyrene gel column. Monodisperse standards of polystyrene are used to generate a calibration graph for evaluating the Mw of unknown samples.

[0049] The polydispersity of the homopolymer (B) is 1.2-4.0. Preferably, the polydispersity of the homopolymer (B) is 1.2 to 3.0.

[0050] The present invention also relates to a novel chemically amplified negative photoresist composition, comprising:

[0051] (a) a mixture of a copolymer (A) and a homopolymer (B), wherein the copolymer (A) and the homopolymer (B) are as defined above;

[0052] (b) a photoacid generator;

[0053] (c) optionally, a base as a quenching agent;

[0054] (d) a solvent or a mixture of solvents;

[0055] (e) optionally, a cross-linking agent; and

[0056] (f) Optionally, additives.

[0057] Based on the total weight of the chemically amplified negative photoresist composition, the preferred content range of the above component (a) (i.e., the mixture of copolymer (A) and homopolymer (B)) is 5 wt %-30 wt %, for example, 5 wt %, 10 wt %, 15 wt %, 20 wt %, 25 wt %, 30 wt %, etc.

[0058] Based on the total weight of the chemically amplified negative photoresist composition, the preferred content range of the above-mentioned component (b) (i.e., the photoacid generator) is 1 wt %-15 wt %, for example, 1 wt %, 2 wt %, 3 wt %, 4 wt %, 5 wt %, 6 wt %, 7 wt %, 8 wt %, 9 wt %, 10 wt %, 11 wt %, 12 wt %, 13 wt %, 14 wt %, 15 wt %, etc.

[0059] Based on the total weight of the chemically amplified negative photoresist composition, the preferred content range of the above component (c) (i.e., optionally, the base as a quencher) is 0.1 wt%-5 wt%, for example, 0.1 wt%, 0.5 wt%, 1 wt%, 1.5 wt%, 2 wt%, 2.5 wt%, 3 wt%, 3.5 wt%, 4 wt%, 4.5 wt%, 5 wt%, etc.

[0060] Based on the total weight of the chemically amplified negative photoresist composition, the preferred content range of the above component (d) (i.e., the solvent or solvent mixture) is 65 wt %-95 wt %, for example, 65 wt %, 70 wt %, 75 wt %, 80 wt %, 85 wt %, 90 wt %, 95 wt %, etc.

[0061] Based on the total weight of the chemically amplified negative photoresist composition, the preferred content range of the above component (e) (i.e., optionally, the cross-linking agent) is 1 wt %-15 wt %, for example, 1 wt %, 2 wt %, 3 wt %, 4 wt %, 5 wt %, 6 wt %, 7 wt %, 8 wt %, 9 wt %, 10 wt %, 11 wt %, 12 wt %, 13 wt %, 14 wt %, 15 wt %, etc.

[0062] Based on the total weight of the chemically amplified negative photoresist composition, the preferred content range of the above component (f) (i.e., optionally, the additive) is 0.1 wt%-5 wt%, for example, 0.1 wt%, 0.5 wt%, 1 wt%, 1.5 wt%, 2 wt%, 2.5 wt%, 3 wt%, 3.5 wt%, 4 wt%, 4.5 wt%, 5 wt%, etc.

[0063] The photoacid generator may be an ionic photoacid generator or a non-ionic photoacid generator.

[0064] The ionic photoacid generator may be Salt compounds, including iodine and sulfonium compounds.

[0065] The nonionic photoacid generator can be an imidosulfonate compound, an N-sulfonyloxyimide compound; a diazosulfonyl compound and other sulfone PAGS, including α,α-methylene disulfone, disulfone hydrazine and disulfonamide salts; a nitrobenzyl compound, a halogenated, especially a fluorinated nonionic PAGS.

[0066] The base may be an organic base, such as an amine or an ammonium salt. For example, the base may be selected from the following: dimethylamine, diethylamine, trimethylamine, triethylamine, tributylamine, dimethanolamine, diethanolamine, trimethanolamine, triethanolamine, tributanolamine, 4-dimethylaminopyridine, dicyclohexylamine, trioctylamine, pyridine, N,N,N',N'-tetrabutylmalonamide and tetramethylammonium hydroxide.

[0067] The solvent can be a ketone, an ether, an ester, and a glycol, such as propylene glycol monomethyl ether acetate, dipropylene glycol monomethyl ether acetate, cyclohexanone, N-methylpyrrolidone, N,N-dimethylacetamide, propylene glycol methyl ether, dibutyl ether, 1-methoxy-2-propanol, diamyl ether, acetone, methyl ethyl ketone, methyl isobutyl ketone, dimethyl ether, diethyl ether, 2-butanone, tetrahydrofuran, 1,2-diethoxyethane, 1,2-dimethoxymethane, diethyl oxalate, butyl lactate, dimethoxyethane, γ-butyrolactone, propylene glycol methyl ether acetate, ethyl lactate, and methyl tert-butyl ether, and combinations thereof.

[0068] The crosslinking agent may be selected from the following: methoxylated cresol, diacetoxycresol and hydroxymethylated glycoluril. The crosslinking agent may be selected from the following: 1,3,4,6-tetrakis(methoxymethyl) glycoluril, 1,3,4,6-tetrakis(ethoxymethyl) glycoluril, 1,3,4,6-tetrakis(butoxymethyl) glycoluril, tris(2,3-epoxypropyl)isocyanurate, 1,3,5-tris(2-hydroxyethyl)isocyanurate, 2,4,6-triallyloxy-1,3,5-triazine, 2,4,6-trimethoxy-1,3,5-triazine, 2,4,6-triethoxy-1,3,5-triazine and tetrakishydroxymethyl glycoluril.

[0069] The additives may be selected from the group consisting of surfactants, stabilizers, dyes and adhesion promoters. For example, the additives may be 309、Silwet L-77、 80. A008, Decaethylene glycol monododecyl ether, 10. L23, S 100, Triton TM X-100, 20. CO-520, CA-630, CO-890, CA-720, ECO 60. Troysol TM S366, F-251, F-257.

[0070] Variation of the content of copolymer (A) and homopolymer (B) in the blend will provide precise control of the polymer composition and address the challenging reduction of line width roughness (LWR).

[0071] The photoresist composition of the present invention can achieve a % reduction in line width roughness (LWR) of greater than 40%, greater than 50%, preferably greater than 60%, preferably greater than 70%.

[0072] Description of the drawings

[0073] Figure 1 Shown is a comparison of the line width roughness (LWR) values ​​of AxB1 (photoresist composition of the invention) and B1 (control photoresist) using a scanning electron microscope (SEM) of a "line and space mode" with a line width of 450 nm. Specific implementation plan

[0074] The following examples illustrate the technical solutions of the present invention and are not intended to limit the scope of the present invention.

[0075] The following synthetic examples are presented to illustrate various compositions. These examples should not be construed as limiting.

[0076] The synthesized polymers were characterized by Waters GPC (Gel Permeation Chromatography) using tetrahydrofuran as carrier solvent. Column calibration was performed using polystyrene standards with molecular weights ranging from 500-50,000 Daltons.

[0077] Example

[0078] Example 1: Synthesis of Copolymer A1

[0079] Poly(4-acetoxystyrene-co-γ-butyrolactone-3-yl methacrylate) (75 / 25, molar ratio): 81.0 g (0.5 mol) of 4-acetoxystyrene, 28.39 g (0.167 mol) of γ-butyrolactone-3-yl methacrylate and 6.0 g of AIBN were dissolved in 400 mL of THF. The resulting solution was degassed and added dropwise to 100 mL of THF at 60° C. under a nitrogen atmosphere over 3.0 h. The solution was further stirred at 60° C. under nitrogen for another 24 h and then cooled to room temperature. The mixture was diluted with 250 ml of THF and added dropwise to 2.5 liters of DI water and stirred. The precipitated polymer was filtered, rinsed with 1.0 L of water and dried at 50° C. under vacuum to produce a white powder (Mw=13,000 and Mw / Mn=2.23).

[0080] Example 2: Synthesis of Copolymer A2

[0081] Poly(4-acetoxystyrene-co-γ-butyrolactone-3-yl methacrylate) (70 / 30, molar ratio): 81.0 g (0.5 mol) of 4-acetoxystyrene, 36.58 g (0.215 mol) of γ-butyrolactone-3-yl methacrylate and 6.0 g of AIBN were dissolved in 400 mL of THF. The resulting solution was degassed and added dropwise to 100 mL of THF at 60° C. under nitrogen atmosphere over 3.0 h. The solution was further stirred at 60° C. under nitrogen for another 24 h and then cooled to room temperature. The mixture was diluted with 250 ml of THF and added dropwise to 2.5 liters of DI water and stirred. The precipitated polymer was filtered, rinsed with 1.0 L of water and dried at 50° C. under vacuum to produce a white powder (Mw=13,500 and Mw / Mn=2.33).

[0082] Example 3: Synthesis of Copolymer A3

[0083] Poly(4-acetoxystyrene-co-methyl methacrylate) (75 / 25, molar ratio): 81.0 g (0.5 mol) of 4-acetoxystyrene, 17.39 g (0.167 mol) of methyl methacrylate and 6.0 g of AIBN were dissolved in 400 mL of THF. The resulting solution was degassed and added dropwise to 100 mL of THF at 60° C. under a nitrogen atmosphere over 3.0 h. The solution was further stirred at 60° C. under nitrogen for another 24 h and then cooled to room temperature. The mixture was diluted with 250 ml of THF and added dropwise to 2.5 liters of DI water and stirred. The precipitated polymer was filtered, rinsed with 1.0 L of water and dried at 50° C. under vacuum to produce a white powder (Mw=12,500 and Mw / Mn=2.28).

[0084] Example 4: Synthesis of Copolymer A4

[0085] Poly(4-acetoxystyrene-co-styrene) (65 / 35, molar ratio): 81.0 g (0.5 mol) of 4-acetoxystyrene, 28.39 g (0.27 mol) of styrene and 6.0 g of AIBN were dissolved in 400 mL of THF. The resulting solution was degassed and added dropwise to 100 mL of THF at 60° C. under a nitrogen atmosphere over 3.0 h. The solution was further stirred at 60° C. under nitrogen for another 24 h and then cooled to room temperature. The mixture was diluted with 250 ml of THF and added dropwise to 2.5 liters of DI water and stirred. The precipitated polymer was filtered, rinsed with 1.0 L of water and dried at 50° C. under vacuum to produce a white powder (Mw=13,000 and Mw / Mn=2.23).

[0086] Example 5: Synthesis of Copolymer A5

[0087] Poly(4-acetoxystyrene-co-hydroxyethyl methacrylate) (75 / 25, molar ratio): 81.0 g (0.5 mol) of 4-acetoxystyrene, 21.73 g (0.167 mol) of hydroxyethyl methacrylate and 6.0 g of AIBN were dissolved in 400 mL of THF. The resulting solution was degassed and added dropwise to 100 mL of THF at 60° C. under a nitrogen atmosphere over 3.0 h. The solution was further stirred at 60° C. under nitrogen for another 24 h and then cooled to room temperature. The mixture was diluted with 250 ml of THF and added dropwise to 2.5 liters of DI water and stirred. The precipitated polymer was filtered, rinsed with 1.0 L of water and dried at 50° C. under vacuum to produce a white powder (Mw=14,000 and Mw / Mn=2.43).

[0088] Example 6: Synthesis of Copolymer A6

[0089] Poly(4-acetoxystyrene-co-hydroxyethyl methacrylate) (70 / 30, molar ratio): 81.0 g (0.5 mol) of 4-acetoxystyrene, 28.00 g (0.215 mol) of hydroxyethyl methacrylate and 6.0 g of AIBN were dissolved in 400 mL of THF. The resulting solution was degassed and added dropwise to 100 mL of THF at 60° C. under a nitrogen atmosphere over 3.0 h. The solution was further stirred at 60° C. under nitrogen for another 24 h and then cooled to room temperature. The mixture was diluted with 250 ml of THF and added dropwise to 2.5 liters of DI water and stirred. The precipitated polymer was filtered, rinsed with 1.0 L of water and dried at 50° C. under vacuum to produce a white powder (Mw=13,000 and Mw / Mn=2.23).

[0090] Example 7: Synthesis of Copolymer A7

[0091] Poly(4-acetoxystyrene-co-hydroxyethyl methacrylate) (60 / 40, molar ratio): 81.0 g (0.5 mol) of 4-acetoxystyrene, 43.46 g (0.334 mol) of hydroxyethyl methacrylate and 6.0 g of AIBN were dissolved in 400 mL of THF. The resulting solution was degassed and added dropwise to 100 mL of THF at 60° C. under a nitrogen atmosphere over 3.0 h. The solution was further stirred at 60° C. under nitrogen for another 24 h and then cooled to room temperature. The mixture was diluted with 250 ml of THF and added dropwise to 2.5 liters of DI water and stirred. The precipitated polymer was filtered, rinsed with 1.0 L of water and dried at 50° C. under vacuum to produce a white powder (Mw=14,500 and Mw / Mn=2.53).

[0092] Example 8: Synthesis of Copolymer A8

[0093] Poly(4-acetoxystyrene-co-hydroxyethyl methacrylate) (50 / 50, molar ratio): 81.0 g (0.5 mol) of 4-acetoxystyrene, 65.07 g (0.5 mol) of hydroxyethyl methacrylate and 6.0 g of AIBN were dissolved in 400 mL of THF. The resulting solution was degassed and added dropwise to 100 mL of THF at 60° C. under a nitrogen atmosphere over 3.0 h. The solution was further stirred at 60° C. under nitrogen for another 24 h and then cooled to room temperature. The mixture was diluted with 250 ml of THF and added dropwise to 2.5 liters of DI water and stirred. The precipitated polymer was filtered, rinsed with 1.0 L of water and dried at 50° C. under vacuum to produce a white powder (Mw=13,600 and Mw / Mn=2.29).

[0094] Example 9: Synthesis of Homopolymer A9

[0095] Poly(4-acetoxystyrene): 81.0 g (0.5 mol) of 4-acetoxystyrene and 6.0 g of AIBN were dissolved in 400 mL of THF. The resulting solution was degassed and added dropwise to 100 mL of THF at 60° C. under nitrogen atmosphere over 3.0 h. The solution was further stirred at 60° C. under nitrogen for another 24 h and then cooled to room temperature. The mixture was diluted with 250 ml of THF and added dropwise to 2.5 liters of DI water with stirring. The precipitated polymer was filtered, rinsed with 1.0 L of water and dried at 50° C. under vacuum to produce a white powder (Mw=16,000 and Mw / Mn=2.73).

[0096] Example 10: Synthesis of Homopolymer B1

[0097] Poly(hydroxystyrene): 10 grams of homopolymer A9 from Example 9, 20 grams of ammonium hydroxide (28-30%) and 100 mL of methanol were heated at 65°C with stirring for 18 h. The resulting solution was precipitated in 500 mL of HCl solution (5%). After stirring for 30 min, the resulting powder was filtered. Rinse with 150 mL of water and dry under vacuum at 50°C to provide a white powder (Mw=12,200 and Mw / Mn=1.85).

[0098] Preparation of Photoresist Compositions (Comparative Photoresist Compositions and Photoresist Compositions of the Invention)

[0099] Four photoresist compositions were prepared and are referred to herein as photoresist compositions A1B1, A3B1, A4B1, and A5B1, respectively.

[0100] The photoresist composition A1B1 contains 40 wt % of copolymer A1 and 60 wt % of homopolymer B1, based on the total weight of copolymer A1 and homopolymer B1.

[0101] Photoresist composition A3B1 contains 25 wt % of copolymer A3 and 75 wt % of homopolymer B1, based on the total weight of copolymer A3 and homopolymer B1.

[0102] Photoresist composition A4B1 contains 20 wt % of copolymer A4 and 80 wt % of homopolymer B1, based on the total weight of copolymer A4 and homopolymer B1.

[0103] Photoresist composition A5B1 contains 50 wt % of copolymer A5 and 50 wt % of homopolymer B1, based on the total weight of copolymer A5 and homopolymer B1.

[0104] In addition, each of the photoresist compositions A1B1, A3B1, A4B1 and A5B1 was prepared as follows: a mixture of copolymer Ax and homopolymer B1 was dissolved in an appropriate solvent (propylene glycol monomethyl ether acetate), and a quencher (tetramethylammonium hydroxide pentahydrate, 0.6 wt % of both polymers), PAG (triphenylsulfonium trifluorosulfonate, 5.0 wt % of both polymers), a crosslinker (Powderlink 1174, at 1-5 wt % of both polymers) and a surfactant (Silwet L7604, at 0.5 wt % of total solids) were added to the resulting solution.

[0105] The formulation of the control photoresist composition was identical except that only homopolymer Bl was used instead of the mixture of copolymer Ax and homopolymer Bl. The control photoresist composition is referred to herein as photoresist Bl.

[0106] All photoresists were prepared at 20 wt% solids in an appropriate solvent (propylene glycol monomethyl ether acetate) and then filtered through a 0.2 μm filter.

[0107]

[0108] Lithography performance

[0109] The photoresist solution was spin coated on a silicon wafer treated with an organic anti-reflective coating of 60 nm thickness. Coating was performed under standard solution spin coating to provide a film with a thickness of 1400 nm after soft baking at 110° C. for 60 seconds. The resulting film was exposed to a 0.53 numerical aperture KrF excimer laser stepper, followed by post-exposure baking at 140° C. for 90 seconds. The resulting film was developed for 40 seconds (20 / 20 second process) using a 0.263N tetramethylammonium hydroxide solution in a double developer surface dwell mode.

[0110] A SEM CG6300 (HITACHI CD-SEM) instrument with the following parameters was used:

[0111] Accelerating voltage 800V Probe current 5.0pA Magnification 149997 Digital zoom 1 Frame rate 16 Image Rotation 0.0 degrees Optics high resolution Pixel 512,512 Automatic EF close Detector ratio 30% Detector Node SE+EF

[0112] The photoresist layers were patterned in a line and space pattern with a line width of 450 nm, and the patterned photoresist layers were analyzed on scanning electron microscope (SEM) images to evaluate their LWR (line width roughness) ( Figure 1 ).

[0113] Figure 1 It is clearly shown that the photoresist composition of the present invention has a lower LWR than that of the comparative example.

[0114] Table 1 LWR of photoresist compositions A1, B1 and B1

[0115]

[0116] Table 2 LWR of photoresist compositions A3, B1 and B1

[0117]

[0118] Table 3 LWR of photoresist compositions A4, B1 and B1

[0119]

[0120] Table 4 LWR of photoresist compositions A5B1 and B1

[0121]

[0122] As can be seen from Tables 1-4 above, the photoresist compositions of the present invention achieve a % reduction in LWR of greater than 40%, preferably greater than 50%, and preferably greater than 60%, compared to the control photoresist composition.

[0123] While the invention has been described with respect to specific embodiments, the details thereof should not be construed as limiting, as it will be apparent that various embodiments, changes and modifications may be made without departing from the spirit and scope thereof, and it should be understood that such equivalent embodiments are intended to be included within the scope of the invention.

Claims

1. A composition comprising a mixture of a copolymer (A) and a homopolymer (B), wherein: The copolymer (A) is an acetoxystyrene copolymer having a dissolution inhibiting acetoxy group and a photoacid dissociable group or a styrene group; and The homopolymer (B) is a hydroxystyrene homopolymer.

2. The composition according to claim 1, wherein the content of the copolymer (A) is in the range of 20 to 80% by weight; and the content of the homopolymer (B) is in the range of 20 to 80% by weight, based on the total weight of the mixture of the copolymer (A) and the homopolymer (B).

3. The composition according to any one of claims 1 to 2, wherein the photoacid dissociable groups contained in the copolymer (A) are selected from the following: alkyl ester groups, alicyclic ester groups or combinations thereof; Preferably, the photoacid dissociable group is selected from the following: an alkyl (meth)acrylate group, an alicyclic (meth)acrylate group, or a combination thereof; Preferably, the photoacid-dissociable group is an alkyl (meth)acrylate group, wherein the alkyl group is selected from the group consisting of methyl, ethyl, propyl, isopropyl, butyl, isobutyl, tert-butyl, pentyl and isopentyl; preferably, the alkyl group is substituted with a hydroxyl group; Preferably, the photoacid dissociable group is an alicyclic (meth)acrylate group selected from a 1-alkyl-1-cycloalkyl (meth)acrylate group and a 2-alkyl-2-adamantyl (meth)acrylate group; Preferably, the photoacid-dissociable group is a 1-alkyl-1-cycloalkyl (meth)acrylate group, wherein the alkyl group is selected from the group consisting of methyl, ethyl, propyl, isopropyl, butyl, isobutyl, tert-butyl, pentyl and isopentyl; and the cycloalkyl group is selected from the group consisting of cyclopentyl, cyclohexyl and cycloheptyl; Preferably, the photoacid cleavable group is a 2-alkyl-2-adamantyl (meth)acrylate group, wherein the alkyl group is selected from the group consisting of methyl, ethyl, propyl, isopropyl, butyl, isobutyl, tert-butyl, pentyl and isopentyl.

4. The composition according to any one of claims 1 to 3, wherein the weight average molecular weight (Mw) of copolymer (A) is 2000-20,000 Daltons; and the polydispersity of copolymer (A) is 1.2-4.0; and wherein the weight average molecular weight (Mw) of the homopolymer (B) is 2000-20,000 Daltons; and the polydispersity of the homopolymer (B) is 1.2-4.

0.

5. The composition according to any one of claims 1 to 4, wherein the acetoxystyrene monomer is in the range of 50 mol% to 90 mol% based on the total moles of the monomers of the copolymer (A); if present, the (meth)acrylate monomer is in the range of 10 mol% to 50 mol% based on the total moles of the monomers of the copolymer (A); if present, the styrene monomer is in the range of 10 mol% to 40 mol% based on the total moles of the monomers of the copolymer (A).

6. A chemically amplified negative photoresist composition comprising: (a) a mixture of a copolymer (A) and a homopolymer (B), wherein the copolymer (A) and the homopolymer (B) are defined in any one of claims 1 to 5; (b) a photoacid generator; (c) optionally, a base as a quenching agent; (d) a solvent or a mixture of solvents; (e) optionally, a cross-linking agent; and (f) Optionally, additives.

7. The chemically amplified negative photoresist composition according to claim 6, wherein the content of component (a) ranges from 5 wt% to 30 wt%, based on the total weight of the chemically amplified negative photoresist composition.

8. A process for producing the chemically amplified negative photoresist composition of any one of claims 6 to 7, comprising mixing each of components (a), (b), (c), (d), (e) and (f).

9. Use of the chemically amplified negative photoresist composition according to any one of claims 6 to 7 for reducing line width roughness.

Citation Information

Patent Citations

  • Positive- and negative-working resist compositions with acid generating photoinitiator and polymer with acid labile groups pendant from polymer backbone

    US4491628A

  • Alkali-soluble siloxane polymer, silmethylene polymer, and polyorganosilsesquioxane polymer

    US4745169A

  • Radiation-sensitive composition

    US5332650A

  • Positive resist material

    US5356753A

  • Chemically amplified positive resist compositions

    US5731126A